The Relationship between Seagrass Density and Macrozoobenthos Abundance in the Waters of Jago-Jago Village, Central Tapanuli Regency, North Sumatra - Ratna Prasetiowati; Joko Samiaji; Efriyeldi Efriyeldi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2026)
This survey was conducted in February - March 2023 in the waters of Jago-Jago Village, Central Tapanuli Regency. This study aimed to determine seagrass density and macrozoobenthos abundance, and to examine the relationship between seagrass density and macrozoobenthos abundance. This research was carried out according to a research method in which the sampling station was determined in a targeted area. Sampling was conducted at 3 research stations using 3 transects perpendicular to the shoreline at each station. Each transect line consists of 3 quadrat plots measuring 1 x 1 m2. The seagrass species found was Enhalus acoroides. The research results showed the highest density at station I (29.44 stands/m2), station II (25.33 stands/m2), and the lowest density was in station III (19.22 stands/m2). These data show that seagrass conditions at stations I and II are sparse, while station III has very sparse conditions. The result shows that the highest density is in station I, at 25.78 ind/m2, and the lowest is in station III, at 6.78 ind/m2. The results of the regression test show that the relationship between seagrass density and macrozoobenthos abundance is significant (p = 0.012) and positive (r = 0.787).